Progesterone Receptor Regulation of Uterine Adaptation for Pregnancy. (July 2018) - Wu, San-Pin; Li, Rong; DeMayo, Francesco J.
Abstract : Progesterone acts through the progesterone receptor to direct physiological adaption of the uterus in preparation and completion of pregnancy. Genome-wide transcriptome and cistrome analyses have uncovered new members and novel modifiers of the progesterone signaling pathway. Genetically engineered mice allow functional assessment of newly identified genes in vivo and provide insights on the impact of progesterone receptor-dependent molecular mechanisms on pregnancy at the organ system level. Progesterone receptor isoforms collectively mediate progesterone signaling via their distinct and common downstream target genes, which makes the stoichiometry of isoforms relevant in modifying the progesterone activity. This review discusses recent advances on the discovery of the progesterone receptor network, with special focus on the endometrium at early pregnancy and myometrium during parturition. Highlights: Progesterone signaling modifiers GATA2 and SOX17 serve as coregulators of PGR to modulate expression of progesterone downstream genes, including Indian Hedgehog. Uterine progesterone signaling is modulated by epigenetic regulators, such as EZH2, KDM5A, and HDAC1, on the expression of progesterone receptor and its downstream targets. Progesterone signaling is transduced by the summary effect of PGR isoform compositions at the target tissues. The two major uterine PGR isoforms, PGR-A and PGR-B, exert distinct functionalities through differential ligand responses, recruitment of coregulators, and modulation of specific sets of downstream target genes. Perturbed progesterone signaling, as demonstrated in multiple genetically engineered mouse models, results in endometrial squamous cell metaplasia with ectopic expression of TP63 that is often seen in endometrial polyps and metaplastic epithelia.